2019
DOI: 10.1021/acs.jpcc.9b07005
|View full text |Cite
|
Sign up to set email alerts
|

The Endocyclic Carbon Substituent of Guanidinate and Amidinate Precursors Controlling Atomic Layer Deposition of InN Films

Abstract: Indium nitride (InN) is an interesting material for future high frequency electronics, due to its high electron mobility. The problematic deposition of InN films currently prevents full exploration of InN based electronics. We present studies of atomic layer deposition (ALD) of InN using In precursors with bidentate ligands forming In-N bonds; tris(N,N-dimethyl-N',N''diisoproprylguanidinato)indium(III), tris(N,N'-diisopropylamidinato)indium(III) and tris(N,N'-diisopropylformamidinato)indium(III). These compoun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…35,38 The lower BE peak at 396.5 eV is assigned to nitrogen in the form of InN. 23,31,32,[35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] For Ar/N 2 -plasma samples, the additional components are at 397.2 and 398.3 eV. The upper component is preserved aer sputtering into the bulk of the lm and can be assigned to an In-N-O bonding environment, which leaves the middle component unassigned.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…35,38 The lower BE peak at 396.5 eV is assigned to nitrogen in the form of InN. 23,31,32,[35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] For Ar/N 2 -plasma samples, the additional components are at 397.2 and 398.3 eV. The upper component is preserved aer sputtering into the bulk of the lm and can be assigned to an In-N-O bonding environment, which leaves the middle component unassigned.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 To date, there have been multiple efforts towards low-temperature InN growth via PE-ALD. 17,[30][31][32][35][36][37][38][39][40][41] Initial epitaxial growth of InN at sub-300 C was achieved by plasma-enhanced atomic layer epitaxy (PE-ALE) where the lms exhibited substrate-dependent varying crystallographic orientations. 17,36 In a relatively recent study, PE-ALD of monocrystalline InN lms has also been reported at 250 C using N 2 -plasma on lower-lattice-mismatched ZnO/Al 2 O 3 substrates, where the lms were fully relaxed with no voids or interlayers at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 ALD of InN has been demonstrated using trimethyl indium (TMI) and either nitrogen plasma 21,22 or NH3 plasma 23 , rendering crystalline InN films. ALD of InN has also been demonstrated using precursors with chelating ligands with In-N bonds, demonstrating polycrystalline 24 or epitaxial InN 25 with NH3 plasma. Recently, we demonstrated that epitaxial and homogeneous wurtzite InN film on 4H-SiC substrate with a thickness down to 5 nm can be grown by using plasma ALD at 320°C, 26 which has never been reported by other growth techniques.…”
Section: Introductionmentioning
confidence: 99%